Association between dietary raw garlic intake and newly diagnosed nonalcoholic fatty liver disease: a population-based study. Issue 6 (December 2019) - Zhang, Shunming; Gu, Yeqing; Wang, Liu; Zhang, Qing; Liu, Li; Lu, Min; Meng, Ge; Yao, Zhanxin; Wu, Hongmei; Xia, Yang; Bao, Xue; Wang, Honglei; et al.
Abstract : Background and Aims: The protective effect of garlic against nonalcoholic fatty liver disease (NAFLD) has been reported in animal studies. However, in humans, the association between garlic consumption and NAFLD is unclear. The study sought to explore the association between habitual raw garlic intake and newly diagnosed NAFLD among Chinese adults. Methods: We performed a study of 11, 326 men and 12, 780 women aged 20–90 years. Habitual food intake was assessed using a validated and standardized 100-item food frequency questionnaire. Diagnosis of NAFLD was based on the liver ultrasonography and self-reported alcohol intake. Multiple logistic regression was used to evaluate the association of raw garlic intake with newly diagnosed NAFLD. Results: The prevalence of newly diagnosed NAFLD was 28.9% in men and 10.1% in women, respectively. In men, the fully adjusted odds ratios (95% confidence interval) of having NAFLD across increasing frequency of raw garlic intake were 1.00 (reference) for <1 time/week, 0.81 (0.73, 0.90) for 1–3 times/week, 0.66 (0.54, 0.80) for 4–6 times/week, and 0.71 (0.55, 0.90) for ≥7 times/week ( P for trend <0.0001). The odds ratio for NAFLD associated with each 1 g of raw garlic/1000 kcal was 0.93 (0.90, 0.97) in men. In women, no significant association between raw garlic intake and NAFLD was identified. These associations between raw garlic intake and NAFLD were consistent in several sensitivity analyses. Conclusions: Frequent consumption of raw garlic is inversely associated with NAFLD in Chinese men. Further investigations are needed to confirm this finding.